Adapting our Flood Risk Policies to Changing Conditions. Issue 10 (2nd February 2021) - Kousky, Carolyn; Kunreuther, Howard; Xian, Siyuan; Lin, Ning
Abstract: Flooding causes more damage and severely impacts more people worldwide than any other natural disaster. Flood risk in many parts of the United States is projected to increase due to both continued floodplain development and climate change. Many of our institutions and public policies are not designed to address these changing risk conditions. The practice of grandfathering insurance premiums in the National Flood Insurance Program (NFIP)—allowing an insured to keep a lower rate even when risk has increased—is one such policy. We link a flood hazard model to a flood insurance premium calculator in order to provide illustrative calculations of the possible impact of grandfathering on program revenue and policyholder premiums due to sea level rise for a New York City neighborhood. We conclude by discussing how to preserve the financial soundness of the NFIP while addressing the affordability of insurance in the face of increasing flood risk.